Electrical performances of commercial GaN and GaAs based optoelectronics under neutron irradiation - Ahmad Fauzi, Dhiyauddin; Alang Md Rashid, Nahrul Khair; Abdul Karim, Julia; Mohamed Zin, Mohamed Rawi; Hasbullah, Nurul Fadzlin; Sheik Fareed, O A (IOP Publishing, 2013)
This paper aims to demonstrate the effects of displacement damage caused by high energetic neutron particle towards the electrical performances of gallium arsenide (GaAs) and gallium nitride (GaN) p-n based diodes. The investigations are carried out through current-voltage (I-V) and capacitance-voltage (C-V) measurements using Keithley 4200 SCS. Two different commercial optoelectronics diodes; GaN on SiC light emitting diode (LED) and GaAs infrared emitting diode (IRED) were radiated with neutron using pneumatic transfer system (PTS) in the PUSPATI TRIGA Mark II research reactor under total neutron flux of 1×1012 neutron/cm2.s. Following the neutron exposure for 1, 3 and 5 minutes, the I-V forward bias and reverse bias leakage current increase for GaAs IREDs, but minimal changes were observed in the GaN LEDs. The C-V measurements revealed that the capacitance and carrier concentration of GaAs IREDs decrease with increasing radiation flux.